Increasing prevalence of overweight and obesity in Yi farmers and migrants from 2007 to 2015 in China: the Yi migrant study - Ye Wang; Li Pan; Shaoping Wan; Huowuli Yi; Fang Yang; Huijing He; Zheng Li; Jia Zhang; Xiaoyang Wang; Zhengping Yong; Guangliang Shan (BMC Public Health, 2018)
Abstract Background With the social development and lifestyle transition, increasing trends of overweight and obesity prevalence are commonly reported worldwide. Data focusing on overweight and obesity trends in rural residents and rural-to-urban migrants in China are limited. This study aims to assess the changes and related factors of overweight and obesity in Yi farmers and migrants in southwest China from 2007 to 2015, and to assess the disparities in prevalence changes. Methods Pseudo-panel data was obtained from two cross-sectional studies conducted in Sichuan province, southwest China in 2007 and 2015. Standardized prevalence of overweight and obesity were evaluated by direct method using the 2010 national census population as the standard. Prevalence differences of overweight and obesity were calculated in each group and compared between groups to evaluate the disparity in prevalence changes. Generalized linear mixed model was performed to determine factors related to overweight/obesity. Results Standardized prevalence of overweight increased in both groups (from 5.54 to 16.65% in Yi farmers, from 27.91 to 33.61% in Yi migrants). Standardized prevalence of obesity increased only in Yi farmers (from 0.37 to 3.13%). Prevalence difference of overweight in Yi farmers was higher than that in Yi migrants (11.11 vs. 5.70), but prevalence differences of obesity were not significantly different between Yi farmers and migrants. Conclusions Prevalence of overweight and obesity in Yi farmers, and prevalence of overweight in Yi migrants increased from 2007 to 2015. Yi farmers were developing overweight at a greater pace than migrants. More attention should be paid to spread health knowledge and encourage healthy lifestyle in Yi people, especially Yi farmers.